Role of oxygen in wetting of copper nanoparticles on silicon surfaces at elevated temperature - Ghosh, Tapas; Satpati, Biswarup (Beilstein Journal of Nanotechnology, 2017)
Copper nanoparticles have been deposited on silicon surfaces by a simple galvanic displacement reaction, and rapid thermal annealing has been performed under various atmospheric conditions. In spite of the general tendency of the agglomeration of nanoparticles to lower the surface energy at elevated temperatures, our plan-view and cross-sectional transmission electron microscopy (TEM), energy dispersive X-ray spectroscopy (EDX) and X-ray diffraction (XRD) analysis shows that the thermal oxidation of the copper nanoparticles and formation of cupric oxide (CuO) on silicon surfaces leads to wetting rather than agglomeration. In contrast, agglomeration has been observed when copper nanoparticles were annealed in a nitrogen environment. The lattice transformation from cubic Cu to monoclinic CuO, and hence the change in surface energy of the particles, assists the wetting process. The occurrence of wetting during the oxidation step implies a strong interaction between the oxidized film and the silicon surface.
Keywords: copper; cupric oxide; electron diffraction; galvanic displacement reaction; oxidation; surface wetting; transmission electron microscopy